Measurements of radon and uranium concentration in water and soil samples from East Anatolian Active Fault Systems (Turkey) - Baykara, O; Dogru, M (Pergamon-Elsevier Science Ltd, 2006)
Different water samples collected from over the North and East Anatolian Fault Systems (NAFS and EAFS) were analyzed for radon concentration, effective radium content and radon exhalation rate using the closed-can technique which includes CR-39 passive detectors and also, annual effective dose have been calculated for the water samples. The uranium concentrations in soil samples were also determined by using Nal(Tl) gamma spectroscopic method. The measured maximum values of the effective radium and radon concentrations in the water samples were 270.5 and 3319.3 Bq/m(3), respectively. However, radon exhalation rate in the water samples varied between 20.2 and 470.0 mBq/m(2) h. The uranium concentrations in soil samples varies between 12.4 +/- 1.2 and 138.0 +/- 6.1 Bq/kg. The highest annual effective doses obtained for radium and radon are 55.1 and 14.5 mu Sv/y, respectively. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: soil; radon; uranium; effective radium content; water; CR-39